Iterative roots of homeomorphisms possessing periodic points - Paweł Solarz (Annales Universitatis Paedagogicae Cracoviensis: Studia Mathematica, 2007)
In this paper we give necessary and sufficient conditions for the existence of orientation-preserving iterative roots of a homeomorphism with a nonempty set of periodic points. We also give a construction method for these roots.